2008
DOI: 10.1021/es703112w
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Carbon Footprint Estimation Boundaries

Abstract: Because of increasing concern about global climate change and carbon emissions as a causal factor, many companies and organizations are pursuing "carbon footprint" projects to estimate their own contributions to global climate change. Protocol definitions from carbon registries help organizations analyze their footprints. The scope of these protocols varies but generally suggests estimating only direct emissions and emissions from purchased energy, with less focus on supply chain emissions. In contrast, approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
240
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(255 citation statements)
references
References 13 publications
3
240
0
12
Order By: Relevance
“…Matthews et al (2008) also demonstrated that only focusing on Scope 1 or Scope 1 and 2 emissions gives significantly lower results for firms than a full Scope 3 approach. Besides Hillman and Ramaswami (2010;also reported in Ramaswami et al, 2008), Kennedy et al (2010) have developed methodology which includes all indirect emissions, including upstream (product-chain) emissions, except from food and materials consumed in cities and emissions upstream of electric power plants.…”
Section: Life Cycle Perspective or Notmentioning
confidence: 94%
See 1 more Smart Citation
“…Matthews et al (2008) also demonstrated that only focusing on Scope 1 or Scope 1 and 2 emissions gives significantly lower results for firms than a full Scope 3 approach. Besides Hillman and Ramaswami (2010;also reported in Ramaswami et al, 2008), Kennedy et al (2010) have developed methodology which includes all indirect emissions, including upstream (product-chain) emissions, except from food and materials consumed in cities and emissions upstream of electric power plants.…”
Section: Life Cycle Perspective or Notmentioning
confidence: 94%
“…The GHG accounts tend to use CO 2 e, including five of the most important GHG in addition to CO 2 (Murakami et al (2011);ICLEI, 2009;IPCC (2006); WRI-WBCSD, 2004). In this respect the methodologies reported in scientific papers differ, since they typically include only CO 2 (Heinonen and Junnila, 2011a;Weber and Matthews, 2008) or CO 2 , CH 4 and N 2 0 (Kennedy et al, 2010;Sovacool and Brown, 2010;Matthews et al, 2008;Ramaswami et al, 2008). It has been argued that using CO 2 is adequate from a practical perspective (Kennedy et al, 2010), since emissions of CO 2 tend to dominate when estimating the contribution of cities to global warming if the target is delimited to GHG emissions within the city boundaries.…”
Section: Ghg And/or Energy Use?mentioning
confidence: 99%
“…Carbon intensities of products have been estimated for industrial and manufactured goods using bottom-up approaches such as LCA (Matthews et al, 2008b). An extensive data search was conducted to collect product carbon intensity factors from multiple data sources (see Table 1).…”
Section: Carbon Intensity Factorsmentioning
confidence: 99%
“…Although this can add considerable complexity, it can also add vital perspective when considering sustainability, since the majority of a product's ecological impact often falls beyond any single tier's organizational boundaries. For example, Matthews et al (2008) estimate that the direct carbon emissions from an industry, on average, represent only 14% of that industry's total supply chain emissions.…”
Section: Forward Supply Chainmentioning
confidence: 99%